In Silico Evaluation of Kaempferol, Gallic Acid, and Stigmasterol from Lagerstroemia speciosa as Multi-Target Antidiabetic Agents: Molecular Docking and Dynamics Simulation Study - Aditya Maulana Perdana Putra; Catherina Adeline Kurniawan; Anna Khumaira Sari; Nabila Hadiah Akbar; Khoirunnisa Muslimawati; Okta Muthia Sari; Dita Ayulia Dwi Sandi; Normaidah Normaidah; Putri Helena Junjung Buih; Ariranur Haniffadli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder that leads to severe complications and continues to increase in prevalence worldwide. Although Lagerstroemia speciosa is a well-recognized antidiabetic medicinal plant, most in silico studies have focused exclusively on its major constituent, leaving the antidiabetic potential of its other phytochemicals largely unexplored. This study investigated the multi-target antidiabetic potential of phytochemicals derived from L. speciosa leaves using an in silico approach targeting three key enzymes: aldose reductase, glucokinase, and glycogen synthase kinase 3-beta (GSK3-β). A total of 62 compounds were screened by molecular docking with AutoDock Vina, followed by toxicity predictions using ProTox-II and ToxTree. The top ligand for each target, kaempferol (aldose reductase), gallic acid (glucokinase), and stigmasterol (GSK3-β), was selected for further evaluation through molecular dynamics simulations using GROMACS 2016.3 for 100 ns. Structural and interaction stability were assessed through RMSD, RMSF, SASA, Rg, and RDF analyses. Binding free energies were calculated using the MM/PBSA method via g_mmpbsa. The results indicated that stigmasterol exhibited the most favorable MM/PBSA binding free energy (–133.377 kJ/mol), followed by kaempferol (–65.714 kJ/mol) and gallic acid (–45.629 kJ/mol). However, this favorable energy was dominated by nonspecific van der Waals contributions, consistent with the diffuse interaction patterns and low hydrogen-bond occupancy (4.24%) for stigmasterol. Kaempferol exhibited the highest hydrogen-bond occupancy (64.38%), indicating a stable, consistent interaction with its target enzyme. Rg and RDF analyses confirmed the compactness and specific atomic interactions of the kaempferol and gallic acid complexes.